THE EFFECT OF VARIOUS LIGHTING INTENSITY TO MN-DOPED TIO2 PHOTOCATALYSIS ACTIVITY IN DELAYING THE RIPENING OF CAVENDISH BANANA (Musa acuminata Group AAA) IN FRUIT STORAGE CHAMBER - Sumendap (NIM : 11214033), Kevin
A recurring problem within the banana industry is handling with the fruitÃ‚Â’s ripening. One of the methods that can be done to lessen the effects of post-harvest ripening is the reduction of ethylene exposure to bananas, as ethylene can cause autocatalytic ripening. Titanium dioxide (TiO2) is a photovoltaic compound capable of degrading ethylene gas through photocatalysis with UV light exposure. Adding manganese as dopant to TiO2 enables it to photocatalyse using visible light. Hence, the aim of this study is to determine the optimal light intensity exposed to TiO2 to procure the highest rate of ethylene degradation; and by extent, the delay of banana ripening. The variation of intesity used in this study is 37, 40, and 54 mW cm-2. The effectiveness of the photodegradation process is measured through the ethylene gas concentration within the fruit storage chamber. The banana ripening is measured through respiration rate, ethylene production rate, carbohydrate content, and peel colour. The results show that light intensity of 40 mW cm-2 gives the best photodegradation activity with ethylene degraded up to 50% . However, its effect on banana ripening delay is not significant observed from the high respiration and ethylene production rate, as well as the similarity of peel colour on the 7th day. Hence, further research is needed to optimise the FSC and TiO2 system.